A New Approach of Perfect Domination in Product of Interval-Valued Fuzzy Incidence Graphs With Application - Kalaiarasi, K.; Geethanjali, P. (Communications in Mathematics and Applications, 2022)
Fuzzy graphs, also known as fuzzy incidence graphs, are a useful and well-organized tool for encapsulating and resolving a variety of real-world situations involving ambiguous data and information. In this investigation article, we introduced the chance of interval-valued fuzzy incidence graphs (IVFIGs) alongside their specific properties. The operations of Cartesian product (CP), Tensor product (TP) in IVFIGs are additionally examined. The technique to compute the degree (DG) of IVFIGs acquired by CP and TP is examined. Some significant hypotheses to figure the DG of the vertices of IVFIGs gained by CP and TP are explained. An innovative idea of perfect domination in CP of two IVFIGs and TP of two IVFIGs utilizing incidence pair are presented and gotten the connection between them. Eventually, genuine utilization of perfect domination number (PDN) to discover which countries (country) have the best education policies among various countries is inspected.
Keywords: . Interval-valued Fuzzy Incidence Graph; Cartesian product of two IVFIGs; Tensor product of two IVFIGs; Perfect dominating set